A New Approach to Model and Optimize the Order Sequence of a Two-stage Storage and Order Picking System with Particular Attention to Restrictions of the Material Flow. (31st May 2016) - Schweitzer, Jens
Abstract: This article shows the fundamental research concerning the modeling and optimizing a two-stage storage and order picking system. Therefore are elected for the type of modeling flexible flowshop problems and for the optimizing method tools as constraint logic programming. For example, it is detected that the sequencing of picking is a major influencing factor in order to increase the picking performance while minimizing the processing times of jobs. Based on a computed program the results are shown for different cases. As a main conclusion, you can estimate the benefit in real cases.